2002
DOI: 10.1590/s1517-74912002000200006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the spatulation of two zinc oxide-eugenol-based sealers on the obturation of lateral canals

Abstract: ABSTRACT:The objective of this research was to evaluate, in vitro, the importance of the correct manipulation of endodontic sealers, correlating it with flow rate and with the consequent obturation of root canals. Twenty-four human canines were prepared, 1 mm from the apex, with K-files up to size 50, by means of the step-back technique. Six lateral canals were then drilled in each tooth, with size 10 file fixed to a low-speed handpiece. The teeth were randomly divided into 4 groups, and root canals were obtur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 8 publications
3
15
0
2
Order By: Relevance
“…The current study was conducted on, human teeth with simulated lateral canals, as proposed by Goldberg, et al 5 (2002) and Pécora, et al . The diameter of the lateral canals artificially prepared in this study corresponded to 150mm, which is in agreement with the diameter of lateral canals reported in former studies 12,15 . Nevertheless, the methodology proposed by Pécora, et al 12 (2002) for preparation of artificial lateral canals was modified in this study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The current study was conducted on, human teeth with simulated lateral canals, as proposed by Goldberg, et al 5 (2002) and Pécora, et al . The diameter of the lateral canals artificially prepared in this study corresponded to 150mm, which is in agreement with the diameter of lateral canals reported in former studies 12,15 . Nevertheless, the methodology proposed by Pécora, et al 12 (2002) for preparation of artificial lateral canals was modified in this study.…”
Section: Discussionsupporting
confidence: 93%
“…The diameter of the lateral canals artificially prepared in this study corresponded to 150mm, which is in agreement with the diameter of lateral canals reported in former studies 12,15 . Nevertheless, the methodology proposed by Pécora, et al 12 (2002) for preparation of artificial lateral canals was modified in this study. To simulate lateral root canals of similar diameter throughout their extension, the active point of the K-file used for preparation of the canals was trimmed until a diameter of 150mm was obtained throughout its extension.…”
Section: Discussionsupporting
confidence: 93%
“…Almedia et al (16) investigated filling ability of different sealers (AH plus, Epiphany, Endomethasone, Pulp Canal Sealer, Sealapex) in lateral canals and found that all sealers flowed into 0.1mm artificial canals by using lateral condensation technique. Pecora et al (26) showed that penetration of a zinc-oxide eugenol sealer into the lateral canals was dependent on the physical properties and the correct manipulation of the sealer. Reader et al (6) found that the plasticized gutta-percha techniques resulted in significantly greater amounts of gutta-percha in lateral canals, whereas lateral and warm lateral condensation techniques produced lateral canals filled with significantly more sealer in resin blocks.…”
Section: Discussionmentioning
confidence: 99%
“…OZE cement is used in various treatments in dentistry and the total quantity of this product can be up, in general, up to 1,250 mg by treatment (Pecora et al, 2002). If this material is totally absorbed, a concentration of up to 0.25 mg/ml in blood is expected in a human patient with 5,000 ml of blood.…”
Section: Discussionmentioning
confidence: 99%
“…OZE cement was first proposed as early as 1855 and has been utilized continuously in various dentistry specialties, including (1) in pediatric dentistry, (2) as a material for the management of removable prostheses, (3) as a temporary obturation material, (4) as a surgical cement in periodontics, and (5) as a sealer in endodontics (Canalda-Sahli et al, 1992;Vieira, 1976;Pecora et al, 2002;Ozalp et al, 2005;Lin et al, 2006). In general, in dentistry procedures, OZE cement is used in the proportion of 1 g zinc oxide and up to 0.25 ml eugenol (Pecora et al, 2002).…”
Section: Introductionmentioning
confidence: 99%